2013
DOI: 10.1039/c3tb20267d
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised polycaprolactone films and 3D scaffolds via gamma irradiation-induced grafting

Abstract: Polycaprolactone (PCL) is frequently used as the base polymer in scaffolds targeted for tissue engineering applications. However, in the absence of further surface modification, the lack of functional moieties on the PCL chain results in non-ideal surface properties of such scaffolds, especially in terms of the inability to tailor the presentation of functional ligands for directed cell adhesion and growth. The current study investigates gamma irradiation-induced grafting as a means of improving the biofunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 50 publications
5
61
0
Order By: Relevance
“…The graft yield for the PCL SC -g-AA film displayed in Table 1 is essentially zero as observed previously when grafting of AA to PCL under similar conditions. 7 The chemical structure of the base polymer, PCL SC , contains both carbon (C 1s peak at 285 eV) and oxygen (O 1s peak at 532 eV) which is evident in all samples along with low (< 2%) levels of silicone contamination (identified through the binding energy of the silicon 2p peak at 101.8 eV). 26 The XPS data for the PCL SC -g-AA film that had been derivatized with PFP is displayed in Table 1 and shows the introduction of both fluorine (F 1s peak at 292 eV) and nitrogen (N 1s peak at 399 eV).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The graft yield for the PCL SC -g-AA film displayed in Table 1 is essentially zero as observed previously when grafting of AA to PCL under similar conditions. 7 The chemical structure of the base polymer, PCL SC , contains both carbon (C 1s peak at 285 eV) and oxygen (O 1s peak at 532 eV) which is evident in all samples along with low (< 2%) levels of silicone contamination (identified through the binding energy of the silicon 2p peak at 101.8 eV). 26 The XPS data for the PCL SC -g-AA film that had been derivatized with PFP is displayed in Table 1 and shows the introduction of both fluorine (F 1s peak at 292 eV) and nitrogen (N 1s peak at 399 eV).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6 In our previous work, it was shown that surface modification throughout three-dimensional (3D) polycaprolactone (PCL) scaffolds (pore sizes of 60−100 μm) could be achieved by graft copolymerization of acrylic acid (AA) using a mixed solvent system, while a methanol solution resulted in surface-confined grafting. 7 In that study, no correlation between wettability and penetration was observed. 7 In addition to introducing site-specific chemistries in porous substrates, there has also been interest in fabricating bifunctional films 8,9 which have shown promise in biomedical applications.…”
Section: ■ Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Higher degree of grafting with increase in concentration generally observed 8,11,12,14,15 and can be rationalised based on radical polymerisation kinetics, i.e. the monomer concentration affects the chain length.…”
Section: Dosementioning
confidence: 98%
“…Successful preparation of these supports ascribes to the signaling domains in the molecules, which can specifically bind to integrin on cell membranes [33]. Various methods consisting of covalent bonding, layer-by-layer self-assembly, plasma treatment, photo-initiated grafting, and γ-irradiationinduced grafting have been utilized to immobilize the biomolecules onto the solid matrix [34,35]. These strategies have several limitations, including low grafting density because of steric hindrance, uncontrollable grafting yield of polymer brushes, and undesired reactions between reactive groups of the brushes and the surface [36].…”
Section: Immobilization Of Huvecsmentioning
confidence: 99%